Polylanguaging practice on writing narrative text: Lexical and structural grammatical cases - Naomi Mars Novelita Batubara; Erwin Ashari; Juwita Boneka Sinaga (University of Muhammadiyah Malang, 2026)
This study considers the polylinguistic practices used by English as a Foreign Language (EFL) learners in writing narratives, with particular attention to lexical and structural elements of grammar. This study also considers the multilingual context of Indonesia and aims to answer questions about how EFL learners utilize their entire linguistic repertoire in translating narratives from Indonesian into English. Using a descriptive research methodology and adopting a research paradigm that leads to generalization, this study was conducted on 13 high school students selected according to the research objectives, and the analysis was carried out on the translated versions of the narrative assignments. Findings reveal that structural polylinguism is a common phenomenon, where students develop English sentences according to grammatical logic in Indonesian. Although the structure is not native to English, it enables students to create coherence and continuity when telling a story. There is also evidence of lexical polylinguism, where students select English words according to Indonesian frameworks, despite the availability of equivalent English words. This is because students rely on meaning rather than lack of vocabulary. In conclusion, this research finds that polylanguaging in narrative writing among students is actually a strategy of meaning-making rather than an expression of grammar mistakes. The implications of these research outcomes indicate that EFL education needs to capitalize on students’ multilingual potentials not just for the development of narratives but also for lifting the anxiety of writing in academic expression.